Techno-economic evaluation of cryogenic networks for separation of CO2 from natural gas - Maqsood, K. (Trans Tech Publications Ltd, 2014)
Different cryogenic networks for the separation of carbon dioxide from natural gas with different feed composition namely, high CO2 content feed and high hydrocarbon feed have been simulated. Equipment sizing and cost estimation has been carried out for the cryogenic networks using the correlation equations provided in the literature. Methane losses and additive requirements in each network has been compared and evaluated. Â© 2014 Trans Tech Publications, Switzerland.